The Role of Family in the Understanding of Islamic Religion Among Students in The Al Falah Tangkahen Junior High School Environment - Taher, Ilit Tarmiji; Hunainah, Hunainah; Supriadi (Al-Mudarris, 2025)
This research aims to explore the role of the family in students' understanding of Islam at Al Falah Tangkahen Middle School and identify the obstacles faced by families in educating children about religion. The method used was interviews with parents and teachers, which revealed that the family serves as an important basis for religious education, where activities such as reading the Koran, discussing religious themes, and celebrating Islamic holidays contribute significantly to understanding. student's religion. However, this research also found several obstacles, such as limited parental time, negative influences from the external environment, and inaccurate information on social media, which can interfere with the religious education process at home. The research results show the importance of collaboration between families and schools to overcome these obstacles and strengthen students' understanding of the Islamic religion. By increasing parental involvement and support from schools, it is hoped that students' understanding of religion can develop optimally.